Principal Component Analysis of Yield and Its Attributing Traits in Recombinant Inbred Lines of Rice Under Submerged Condition (Oryza sativa L.) - Lakshmeesha R,; Mahesh, H.B.,; , Basavaraj M Pattanashetti; , K.M. Harinikumar; , Veena S Anil (Archives of Current Research International, 2024)
Rice, Oryza sativa L., is the world's most important staple crop, feeding more than half of the world's population. The phenotype of plant is the result of interaction of many factors and final yield is the sum of total effect of several component factors. Therefore evaluation of genetic variability forms the basis for any crop improvement programme, the success of which depends on sufficient genetic variability among genotypes so as to permit effective selection. Hence Evaluation of Principle Component Analysis (PCA)of recombinant inbred lines (RILs) was done at phenotypic level under submerged conditions to reduce a large series of data into smaller number of components by looking for groups that have very strong inter-correlation in a set of variables and each component explained per cent variation to the total variability. The RIL population was derived from an inter-specific cross between BPT5204 and HPR14 parents. A study was conducted using 1256 Recombinant Inbreed Lines submerged condition in the two seasons at College of Agriculture V.C. Farm, Mandya with nine agro-morphological traits and a principle component analysis was carried out. Out of nine principle components, four exhibited Eigenvalue more than one governing 77.74% variance and 69.86% variance in the summer and kharif seasons respectively. The highest positive Eigenvalue was observed for total number of tillers, productive tillers, non-productive tillers and fallowed by single plant yield in PC1 in the summer and kharif season respectively. The highest positive Eigenvalue was observed for five panicle weight, single panicle length, single plant yield and plant height in PC2 of summer and kharif season respectively. Indicating their pronounced effect on the overall variation in the Recombinant Inbreed Lines of Rice.